Face to Face with Anti-Muslim Sentiment: A Qualitative Study into the Coping Mechanisms of Young College and University Muslim Students and Graduates in Flanders - Ans De Nolf; Leen d’Haenens; Abdelwahed Mekki-Berrada (Religions, 2021)
This explorative study seeks to provide insights into the ways young Muslim adults experience and cope with Islamophobia in Flanders. For this purpose, in-depth interviews with 14 Muslims aged 19 to 33 were conducted in the spring of 2020. Our interviewees defined themselves as Muslims and all had been confronted with racism or anti-Muslim sentiment in their daily life. Depending on reported intentions, we identified seven coping strategies in the face of such sentiment: relativization, avoidance, communication, oppression, conciliation, reaction and passive coping strategies. These forms of coping are not mutually exclusive. They are often used in combination, and they may be interchangeable in some situations. This study seeks to complement and deepen the existing literature on anti-Muslim sentiment in Flanders. Its findings should be considered as a starting point for further deductive testing of the identified typologies, meant to inspire follow-up research and serve as evidence for future policymaking.